Development of probiotic fruit juice powders by spray-drying: a review - Barbosa, Joana (2017)
The use of spray-drying for the production of powdered fruit juices has been a common practice in recent years since it is a simple, economic, and advantageous technique. The current knowledge on the different spray-drying parameters, allowing the best conditions to obtain high-quality powders, is presented in this review. The incorporation of probiotic cultures into fruit juices can enhance the functional characteristics of fruit juices. The selection of these probiotics and their benefits to consumers' health are briefly discussed. As maintaining the viability of probiotics is extremely important in the development of a probiotic functional product, the factors that influence and improve survival, in all pre- and post-spray-drying steps, are also detailed. Finally, a few studies on probiotic fruit juices obtained by spray-drying are cited. Industries should bet on their development and commercialization, since despite being challenging to develop, these are very innovative and attractive products meeting modern consumer demands.